Plato's forms in transition : a reading of the Parmenides - Rickless, Samuel Charles, 1964- (Cambridge University Press, 2007)
Samuel Rickless argues that the main point of Plato's Parmenides is to change our conception of the Forms by granting that they can have contrary properties. With the help of his study, we can understand exactly why Plato wrote the Parmenides and what role it played in his philosophical development.